Shear bond strength of orthodontic brackets bonded with glass ionomer cement - Mitić Vladimir (Serbian Medical Society - Dental Section, Belgrade, 2009)
Introduction. A great number of techniques have been used for bonding orthodontic brackets to the tooth surfaces. Glass ionomer cements are frequently used material for this purpose. The aim of this study was to measure the shear bond strength of orthodontic brackets bonded with glass ionomer cement Ortho Fuji LC and remained adhesive on the enamel surface after brackets debonding. Material and methods. A total of 40 extracted premolars for orthodontic reasons in different gender patients, 10-16 years old, were randomly divided into four groups. Using glass ionomer cement Ortho Fuji LC (Tokyo, Japan) stainless steel brackets were bonded to the teeth with the average surface area of the bracket base of 14.7 mm2. The shear bond strengths were measured at a crosshead speed of 1 mm per minute, and the load applied at the time of fracture was recorded using electronic dynamometer. Remained adhesive on the enamel after bracket debonding was evaluated using the adhesive remnant index (ARI). Results. Shear bond strength had the highest value for the group where enamel was etched right before bonding bracket (9.14 MPa), than in the group 2 (7.43 MPa), while in the groups 1 (6.72 MPa) and 3 (6.22 MPa), where etching was not performed, bond strength was lower. Conclusion. Shear bond strength of orthodontic brackets bonded with glass ionomer cement Ortho Fuji LC had higher values when the enamel was etched than without etching.